Arcade catastrophe - Mull, Brandon, 1974- (Mull, Brandon, 1974- Candy shop war, 2014)
Nate and his friends think the new Arcadeland, where tickets can earn jets, tanks, subs, and racecars, is totally cool, until they learn that the arcade owner is hiding a secret.